The second species of Phanoperla (Plecoptera: Perlidae) from China, P. hainana sp. nov., from Hainan Island - Li, Weihai; Qin, Xuefeng (Zootaxa, 2016)
The genus Phanoperla Banks was originally established as a subgenus of Neoperla and its genus delimitation was not fully clear until the revisionary work by Zwick (1982). It currently contains 49 known species from the Oriental region (Banks 1938, 1939, Cao & Bae 2009, Cao et al. 2007, DeWalt et al. 2016, Jewett 1975, Kawai 1968, Stark 1983, 1987, Stark & Sheldon 2009, Sivec & Stark 2010, 2011, Stark & Sivec 2007, Sivec et al. 1988, Zwick 1982, Zwick 1986, Zwick & Sivec 1985). Although species of Phanoperla are not rare in many areas of Southeast Asia bordering China, especially Vietnam and India (Cao & Bae 2009, Mason & Stark 2015), P. pallipennis Banks, 1938 is the only known species of the genus known from China. In this paper, we describe a new species of Phanoperla from Hainan Island of the southernmost province of China. The northern portion of the island has a humid subtropical climate, whereas the remainder of the island has tropical monsoon climate.